Representasi Ideologi Feminisme dalam Film Animasi Encanto: Sebuah Kajian Semiotika - Cattleya Wahyu Pravitha; Irene Evi Krismawati; Ali Mustofa (Jurnal Bahasa dan Sastra, 2023)
The animated film Encanto, which told the narrative of a magical Colombian family, introduced a new paradigm in the representation of women in the film industry. The unconventional female characters in this Disney-produced picture drew public notice and helped it win Academy Awards.  The multiple feminisms represented by these female figures are investigated descriptively and qualitatively. Data were gathered by watching the sequences of Encanto's film and paying attention to how feminism is depicted; taking pictures of each scene that depicts feminism; and then inventorying the acquired data. The data was evaluated and classified according to the feminism depicted in the scenes and discussions using John Fiske's semiotic theory. Existentialist Feminism, Postmodern Feminism, Psychoanalytic Feminism, and Ecofeminism Feminism were discovered to be the feminism streams portrayed in Encanto's animated films. These diverse streams of feminism are a breath of fresh air, breaking the preconceptions of female protagonists in prior Disney animated films.